Eliciting risk preferences: Firefighting in the field - Utteeyo Dasgupta; Subha Mani; Smriti Sharma; Saurabh Singhal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Heterogeneity in subject populations often necessitates choosing an elicitation task that is intuitive, easy to explain, and simple to implement. Given that subject behaviour often differs dramatically across tasks when eliciting risk preferences, caution needs to be exercised in choosing one risk elicitation task over another. Using a within-subject design, we compare behaviour in the simple most investment game (Gneezy and Potters 1997) and the ordered lottery choice game (Eckel and Grossman 2002) to evaluate whether the simpler task allows us to elicit attitudes consistent with those elicited from the ordered lottery task. Using a large sample of over 2000 subjects, we find risk attitudes to be fairly stable across the two tasks. Our results further indicate that the consistency of risk attitudes across the tasks depends on gender of the subject, quantitative skills, father's education level, and dispositional factors such as locus of control and Big Five personality traits.
Keywords: C91; C81; D81; 330; risk preferences; experiment design; elicitation methods; personality traits; India